(untitled) (Critical Romani Studies, 2025)
Romani communities across Europe face pervasive environmental racism. Among the most notorious of such cases is the lead poisoning of displaced Roma, Ashkali, and Egyptians in camps managed by the United Nations Mission in Kosovo (UNMIK) from 1999–2013. This article focuses on the victims’ efforts to seek justice through the UN’s accountability mechanisms – the only avenue available due to the UN’s immunity – and examines the opportunities and limitations inherent in pursuing justice through legal processes. After a decade-long legal battle, the UN’s Human Rights Advisory Panel issued a landmark decision finding UNMIK responsible for human rights violations linked to the lead poisoning. We analyze the decision as an important instrument for reframing the issue from victim-blaming to exposing the role of anti-Romani racism in enabling environmental injustice. Despite the hard-earned victory, however, the Panel’s decision has yet to yield reparations for the Romani victims. We argue that this outcome reflects the limitations of legal bodies as hegemonic institutions, which make them inherently imperfect tools for redressing systemic racism. This reality underscores the importance of combining legal efforts with out-of-court advocacy by Romani communities and solidarity partners to achieve systemic change.